The human DEPhOsphorylation Database DEPOD: 2019 update. (14th December 2019) - Damle, Nikhil P; Köhn, Maja
Abstract: The human Dep ho sphorylation D atabase (DEPOD) is a manually curated resource that harbors human phosphatases, their protein and non-protein substrates, dephosphorylation sites and the associated signaling pathways. We report here an update to DEPOD by integrating and/or linking to annotations from 69 other open access databases including disease associations, phosphorylating kinases, protein interactions, and also genome browsers. We also provide tools to visualize protein interactions, protein structures, phosphorylation networks, evolutionary conservation of proteins, dephosphorylation sites, and short linear motifs within various proteins. The updated version of DEPOD contains 254 human phosphatases, 336 protein and 83 non-protein substrates, and 1215 manually curated phosphatase-substrate relationships. In addition, we have improved the data access as all the data in DEPOD can now be easily downloaded in a user-friendly format. With multiple significant improvements, DEPOD continues serving as a key resource for research on phosphatase-kinase networks. Database URL : www.depod.org